Analisis Perlakuan Akuntansi Aset Biologis Berbasis PSAK 69 (Studi Kasus Pada Peternakan UD Wibowo Farm Kabupaten Blitar) - Latifa Nur Aini; Meta Ardiana (Prodi Akuntansi Fakultas Ekonomi Universitas Hasyim Asy'ari, 2020)
This study aims to determine the accounting treatment of biological assets in the form of recognition, measurement, and also disclosures in the financial statement of biological assets at Wibowo farm in Blitar District. In this study researchers used qualitative research methods in which researcher will observe the object in the field directly in order to obtain existing data and are also needed in research. The results of this study indicate that Wibowo Farm which engaged in laying hens has not yet fully applied the accounting treatment of biological assets based on PSAK No.69. Measurement of biological assets measured at fair value is in accordance with PSAK 69, but they haven’t journalized every transaction in accordance with PSAK. They only record simple purchase transactions. Wibowo Farm also doesn’t present and also disclose biological assets in the annual financial statement. They experience difficulties and limited time so that the basic financial statement rules have not yet been applied.